A computer-aided approach improving the Axiomatic Design theory with the distributed design resource environment. Issue 1 (9th February 2020) - Chen, Bin; Hu, Jie; Qi, Jin; Chen, Weixing
Abstract: In the traditional Axiomatic Design (AD) theory, the mapping from the functional domain to the physical domain is based on the designers' own knowledge and experience, and there is no systematical approach including the design resources provided outside the designers themselves' access. Thus, the raw materials for the design process are largely limited, which means they can hardly support the designers' increasingly creative and innovative conceptions. To help AD theory better support the design process, this paper proposes a computer-aided approach for the mapping from the functional domain to the physical domain within a distributed design resource environment, which consists of numerous design resources offered on the Internet by the providers widely distributed in different locations, institutes, and disciplines. To prove the feasibility of this proposed approach, a software prototype is established, and a natural leisure hotel is designed as an implementation case.